Use of non-steroidal anti-inflammatory drugs and nutritional supplements in Zimbabwean football - Mkumbuzi, N S (South African Journal of Sports Medicine, 2015)
Background. The use of medications by football players in many populations is known to be high. Data on African players are scarce. Objective. To determine the magnitude of use of non-steroidal anti-inflammatory drugs (NSAIDs) and nutritional supplements by Zimbabwean football players. Methods. We conducted a cross-sectional study during the 2011/2012 Premier Soccer League football season. A total of 86 players responded to a self-administered questionnaire that assessed self-reported use of NSAIDs and nutritional supplements. Results. All the participants admitted to taking NSAIDs, with 44% self-prescribing. Nutritional supplements were taken by 56% of the respondents. Of these, 21% took them on a daily basis and 40% did so without professional advice. Conclusion. Regular, self-prescribed use of NSAIDs and nutritional supplements is high among Zimbabwean football players.